UNDESCENDED TESTIS, DIAGNOSIS AND TREATMENT - Winarta Lesmana Handrea (Universitas Udayana, 2013)
Undescended testis (UDT) or cryptorchidism is one of the commonest abnormalities in male infants. In this anomaly, testes are not located normally in the scrotum. The incidence of UDT is 4-5% of term male infants, and 20-33% of premature male infants. The occurrence of abnormalities of hormones control or anatomy process that is required in the normal process of lowering the testes can cause UDT. UDT can be differentiated into palpable and nonpalpable. The diagnosis of UDT can be known through physical examination. However, if the testes are impalpable, laparoscopy can be done to determine the position of the testis. Hormonal therapy to overcome UDT is still under controversy. The action that often done is surgery, called orchidopexy. The most serious complication of orchidopexy is testicular atrophy. It occurs in a small percentage, which is about 5-10%. Infertility may occur in 1 to 3 of 4 adult males and the risk of occurrence of malignancies is increased by as much as 5-10 times higher in men with a history of UDT.